Antioxidant and Anticancer Activities and Protein Interaction of the Oxidovanadium(IV) Naringin Complex - Restrepo Guerrero, Andrés Gonzalo (2022)
The complex of oxidovanadium(IV) with naringin (Narg) [VO(Narg)₂] 8H₂O (VONarg) was prepared according to the literature improving the synthetic procedure and physicochemical characterization. In addition, biological activities (cytotoxic, antioxidant, and BSA interaction) were determined. The metal coordinated through the 5-hydroxy and 4-carbonyl groups of rings A and C of naringin, respectively. The antioxidant activity of VONarg, determined in vitro, was higher than those of the flavonoid against superoxide and peroxyl reactive oxygen species (ROS) and DPPH radical. The cytotoxic properties were determined by a MTT assay on adenocarcinoma human alveolar basal epithelial cells (A549). VONarg exerted a 20% decrease in cancer cells viability at 24 h incubation, while naringin and oxidovanadium(IV) cation did not show cytotoxicity. Measurements with the normal HEK293 cell line showed that the inhibitory action of the complex is selective. VONarg generated intracellular reactive oxygen species (ROS), depletion of reduced glutathione and depolarization of mitochondrial membrane potential, typical for apoptotic pathway, producing cell death by oxidative stress mechanism. Moreover, naringin interacted with bovine serum albumin (BSA) through hydrophobic interactions in a spontaneous process, and VONarg showed greater affinity for the protein but can still be transported and delivered by it (Kₐ 10⁴ L⋅mol⁻¹ order).